Educating for human dignity : learning about rights and responsibilities - Reardon, Betty (Philadelphia : University of Pennsylvania Press, 1995)
Issues of universal human rights are critically important topics in education today. Educators, scholars, and activists urge schools to promote awareness and understanding of human rights in their curricula from the earliest levels. Written by Betty A. Reardon, one of the foremost scholars on human rights education for the primary and secondary levels, Educating for Human Dignity is designed for both teachers and teacher educators. It is the first resource offering both guidance and support materials for human rights education programs from kindergarten through high school. It opens possibilities for an holistic approach to human rights education that directly confronts the values issues raised by human rights problems in a context of global interrelationships.
Introduction: purposes and approaches -- Developmental sequence for presentation of the core concepts -- Early grades: laying the foundation for an appreciation of human dignity -- Kindergarten to grade three -- Middle grades: introducing standards and principles -- Grades four to six -- Junior high school: reflecting and valuing -- Grades seven to nine -- Senior high school: confronting the problems, taking responsibility -- Grades ten to twelve -- Resources for human rights education -- Appendix: selected human rights documents.
"A K-12 teaching resource"--Cover.
Filmography: pages 218-220.
Includes bibliographical references (pages 206-217) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Human rights -- Study and teaching; Droits de l'homme (Droit international) -- Étude et enseignement; POLITICAL SCIENCE -- Human Rights; Human rights -- Study and teaching; Mensenrechten; Onderwijs; Onderwijsprojecten